Remembering New Words: Integrating Early Memory Development into Word Learning - Wojcik, Erica H. (Frontiers in Psychology, 2013)
In order to successfully acquire a new word, young children must learn the correct associations between labels and their referents. For decades, word-learning researchers have explored how young children are able to form these associations. However, in addition to learning label-referent mappings, children must also remember them. Despite the importance of memory processes in forming a stable lexicon, there has been little integration of early memory research into the study of early word learning. After discussing what we know about how young children remember words over time, this paper reviews the infant memory development literature as it relates to early word learning, focusing on changes in retention duration, encoding, consolidation and retrieval across the first two years of life. A third section applies this review to word learning and presents future directions, arguing that the integration of memory processes into the study of word learning will provide researchers with novel, useful insights into how young children acquire new words.